2018
DOI: 10.1108/aaaj-04-2016-2540
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder interactions and corporate social responsibility (CSR) practices

Abstract: Purpose The purpose of this paper is to critically explore the interactions of key stakeholders and their impact upon corporate social responsibility (CSR) practices in the Zambian copper mining sector. In particular, the authors examine the power dynamics that emerge in the stakeholder interactions. Design/methodology/approach The authors analyse the stakeholder interactions based on the varying degrees of stakeholder salience and critical collaboration potential, and draw on rich evidence from 43 interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 90 publications
2
58
1
1
Order By: Relevance
“…In order to make a comprehensive evaluation, this paper evaluates CER from five dimensions: legal consciousness, social evaluation, eco‐friendly production, low‐carbon technology, and green management (Kim et al, ; Kolk, ; Liu et al, ; Phiri et al, ; Reyes‐Rodríguez et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to make a comprehensive evaluation, this paper evaluates CER from five dimensions: legal consciousness, social evaluation, eco‐friendly production, low‐carbon technology, and green management (Kim et al, ; Kolk, ; Liu et al, ; Phiri et al, ; Reyes‐Rodríguez et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We exclude firm-years that are missing necessary data for the variables used in our analysis. We end up with a sample of 4,464 In order to make a comprehensive evaluation, this paper evaluates CER from five dimensions: legal consciousness, social evaluation, eco-friendly production, low-carbon technology, and green management (Kim et al, 2017;Kolk, 2016;Liu et al, 2015;Phiri et al, 2019;Reyes-Rodríguez et al, 2016).…”
Section: Corporate Innovation and Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…While some researchers have shown that CSR is impacted by the local specificities of laws, cultures, and beliefs, others have focused on the relationship between CSR reporting and particular industries. However, accounting researchers have tended to focus on heavy polluters in oil and gas (Herremans and Nazari, 2016;Ness and Mirza, 1991), mining (Adler et al, 2017;Phiri et al, 2019), water (Vinnari and Laine, 2013), and electricity generation (Alrazi et al, 2016), as well as important service sectors like banking and finance (Haigh, 2006). In each case, the reports have been analyzed in relation to each industry's own specific arrangement of environmental, social, and labour issues (McPhail and Adams, 2016).…”
Section: Descriptive Research: What Is Csr Reporting?mentioning
confidence: 99%
“…However, while there is a growing CSR interest by banks in Zambia, little is known on how bank customers perceive CSR activities especially its effect on buyer behaviour. A review of the literature indicates that the most of the research that has been done on CSR in Zambia has focused on the mining sector (e.g., Noyoo, 2010;Phiri et al, 2019;Cronje et al, 2017). As such, questions on whether bank customers appreciate CSR activities and how CSR affects buyer behaviour in developing economies in general and Zambia in particular remain unanswered.…”
Section: Literature Review Theoretical Framework and Hypotheses Devementioning
confidence: 99%